A note on Kohlsia graphis erana from Costa Rica - Arnold, Keith; Tonn, Robert J. (Revista de Biología Tropical, 1964)
During a survey of ectoparasites of birds and mammals of Costa Rica, conducted by the International Center for Medical Research and Training, two males and two females of the flea Kohlsia graphis (Rothschild) were collected from two Tropical Red Squirrels, Sciurus granatensis.